Solving unit commitment with wind power using artificial immune evolutionary programming optimization technique: article / Mohamad Fitri Ramli - Ramli, Mohamad Fitri
This paper propose a solution to unit commitment problem with wind power using artificial immune evolutionary programming The objective of this paper is to find the suitable generation scheduling which can minimize the operation cost with subjmted to various constrain The main idea of this paper is to integrate the use of Artificial fmmune Evolutionary Programming as optimization technique towards Unit Commitment Other than that, this paper also aiming to ieview the effect of addition wind power to the Unit Commitment problem solution. MATLAB prugramming lenguage was used to execute the prngram using l0 set of generator daa with several constrain like power balancg and generation limit .The process of Artificid Immure Evolutionary Programming including of initialization, cloning cost calculation, mutation, sorting and combine and convergences test The result are shown to verify the performance of Artificial Immune Evolutionary Programming technique